How does a domestic tax reform affect protection against imports? : The case of the Republic of Madagascar - Hallaert, Jean-Jacques (IMF Working Papers; Working Paper, 2008)
In 2008, Madagascar reformed its domestic tax system. Because the excise duties and VAT regimes were reformed, the taxation of imports has changed. This paper quantifies how the reform changes the protection against imports and the fiscal revenues from taxation of imports. It shows that, even if the reform has only a limited impact on the average rate of protection, it substantially alters the structure of protection across goods. Moreover, because the reform further increases the already high rate of taxation of imports, it will also boost revenue from taxes on imports and reduce the fiscal losses from the SADC FTA.